Low Noise Figure 2.4 GHz Down Conversion CMOS Mixer for Wireless Sensor Network Application - Murad, S.A.Z.; Sapawi, R. (IEEE, 2017)
This work proposed a low noise figure 2.4 GHz down-conversion CMOS mixer for wireless sensor network (WSN) application using 0.13-μm Silterra technology. The proposed down-conversion mixer converts a high radio frequency (RF) signal from 2.4 GHz to an intermediate frequency (IF) of 100 MHz through the use of a local oscillator signal (LO) of 2.3 GHz. The proposed mixer employs a double balance Gilbert-cell topology with integrated input matching at the input stage and a low pass filter at the IF stage. The simulation results indicate that the proposed mixer obtains lower noise figure (NF) of 5.21 dB with an input third-order intercept point (IIP3) of 0 dB. Furthermore, the conversion gain (CG) of 8.6 dB is achieved